Response of aryloxyphenoxypropionate-resistant grain sorghum to quizalofop at various rates and application timings - Abit, Mary Joy M.; Al-Khatib, Kassim; Stahlman, Phillip W.; Geier, Patrick W. (My University, 2013)
Conventional grain sorghum is highly susceptible to POST grass control herbicides. Development of aryloxyphenoxypropionate-resistant grain sorghum could provide additional opportunities for POST herbicide grass control in grain sorghum. Field experiments were conducted at Hays and Manhattan, KS, to determine the effect of quizalofop rate and crop growth stage on injury and yield of aryloxyphenoxypropionate-resistant grain sorghum. Quizalofop was applied at 62, 124, 186, and 248 g ai haˉ¹ at sorghum heights of 8 to 10, 15 to 25, and 30 to 38 cm, which corresponded to early POST (EPOST), mid-POST (MPOST), and late POST (LPOST) application timings, respectively. Grain sorghum injury ranged from 0 to 68% at 1 wk after treatment (WAT); by 4 WAT, plants generally recovered from injury. The EPOST and MPOST applications caused 9 to 68% and 2 to 48% injury, respectively, whereas injury from LPOST was 0 to 16%, depending on rate. Crop injury from quizalofop was more prominent at rates higher than the proposed use rate in grain sorghum of 62 g ha-1. Grain yields of quizalofop treatments were similar with the non-treated treatments and that application of quizalofop at different timings did not reduce yield except when applied MPOST at the Manhattan site.
Citation: Abit, M. Joy M., Kassim Al-Khatib, Phillip W. Stahlman, and Patrick W. Geier. “Response of Aryloxyphenoxypropionate-Resistant Grain Sorghum to Quizalofop at Various Rates and Application Timings.” Weed Technology 26, no. 1 (March 2012): 14–18. https://doi.org/10.1614/WT-D-11-00020.1.
Keywords: Quizalofop; Sorghum; ACCase-inhibiting herbicides; Growth stages; Application timing; Herbicide rate; Crop response